Methodological alternative for strengthening school coexistence - Urbay Rodríguez, Marilin; Pérez Ramírez, Cecilia (PEM. Revista de Didáctica, Evaluación e Innovación, 2024)
The research solves a scientific problem of great importance for the school context. School coexistence is conceived as the process of interrelation between the agents of an educational institution within a democratic environment, of respect, tolerance and inclusiveness that allows to coexist and resolve conflicts peacefully through dialogue and assertive negotiation. It is a complex category, linked to high self-esteem, which can be learned as part of a broad process of emotional development. The methodological alternative is distinguished by conceiving the diagnosis as a starting point for the transformation of practice from the personal cognitive, attitudinal and moral values, supported by the development of coexistence from a vision of changes in behavior, with the objective of offering teachers/tutors a pedagogical tool for guidance in relation to the teaching and learning of coexistence. Methods of the theoretical, empirical and statistical mathematical level are used that allowed to verify the magnitude of the problem and justify the feasibility of the solution to it. Recommendations are made to systematize them through practical intervention by means of an experimental approach.